Dikotomi Ilmu Agama dan Umum dalam Pendidikan Islam: Implikasi Epistemologis dan Upaya Integrasi Ilmu - La Ode Kou; Mirna Mirna; Nurhayati Ali (FKIP, Universitas Palangka Raya, 2026)
This study examines the dichotomy of religious and general knowledge in the context of Islamic education, as well as its epistemological implications for efforts to integrate knowledge. The dichotomy of knowledge, which separates religious knowledge (ilmu syar'iyyah) from general knowledge (ilmu kauniyyah), has become a profound issue affecting Islamic education in various parts of the world, including Indonesia. Using a qualitative approach based on library research, this study analyzes the historical and epistemological roots of this dichotomy and its impact on the development of holistic Islamic education. The results indicate that this separation of knowledge stems from the influence of colonialism, the secularization of education, and the epistemological crisis experienced by Muslims. This study also reveals that, from an Islamic perspective, knowledge should be viewed as an integral whole, with both religious and general knowledge originating from the same source, namely Allah SWT, and should not be separated. Therefore, this study offers a solution for integrating knowledge based on the epistemology of monotheism, with the hope of reconstructing the Islamic education system to be more harmonious, interdisciplinary, and relevant to the needs of the times. This integration is expected to strengthen the development of a more advanced Islamic civilization by combining religious values ​​and scientific advancement.